2018
DOI: 10.18203/2320-6012.ijrms20182043
|View full text |Cite
|
Sign up to set email alerts
|

Clinico epidemiological and mycological study of pityriasis versicolor PITYRIASIS VERSICOLOR

Abstract: Background: Pityriasis versicolor, a chronic superficial fungal infection caused by lipophilic yeasts of the genus, Malassezia is a common infection in the tropical and subtropical regions. Objective was to study the epidemiology, clinical presentation, associations, etiological agents and clinico-mycological correlation of pityriasis versicolor. 
Methods: Hundred patients with clinical diagnosis of pityriasis versicolor who attended the mycology out-patient (OP) clinic between September 2014 and August 2015 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…We found multiple achromic/hypopigmented (50%), chromic/ hyperpigmented (25.9%) and erythematous (7.6%) macules. Similarly, Snekavalli 32 (achromic 68%; chromic 23%; mixed 9%), Kabbin et al 25 12 (62.9%) found hypopigmented macule as the most common presentation in PV. There are several hypotheses to explain the presence of various colours of macules in PV.…”
Section: Figure: 3 Morphological Appearance Of Malassezia Species In ...mentioning
confidence: 86%
See 2 more Smart Citations
“…We found multiple achromic/hypopigmented (50%), chromic/ hyperpigmented (25.9%) and erythematous (7.6%) macules. Similarly, Snekavalli 32 (achromic 68%; chromic 23%; mixed 9%), Kabbin et al 25 12 (62.9%) found hypopigmented macule as the most common presentation in PV. There are several hypotheses to explain the presence of various colours of macules in PV.…”
Section: Figure: 3 Morphological Appearance Of Malassezia Species In ...mentioning
confidence: 86%
“…[3] We noted mild pruritus in 44.2% cases. But Snekavalli et al 32 showed pruritus in 32% and Rao et al 23 33 Ghosh et al demonstrated diabetes mellitus in 2.73% and lymphoproliferative malignancy in 1%. 1 Another study showed diabetes mellitus in 39.3% and hypertension in 25% of the participants.…”
Section: Figure: 3 Morphological Appearance Of Malassezia Species In ...mentioning
confidence: 97%
See 1 more Smart Citation